Interleukin-17A and interleukin-22 production by conventional and non-conventional lymphocytes in three different end-stage lung diseases - Albrecht, Melanie; Halle, Olga; Gaedcke, Svenja; Pallenberg, Sophia T; Camargo Neumann, Julia; Witt, Marius; Roediger, Johanna; Schumacher, Marina; Jirmo, Adan Chari; Warnecke, Gregor; Jonigk, Danny; Braubach, Peter; et al. (Clinical & Translational Immunology, 2022)
Objectives The contribution of adaptive vs. innate lymphocytes to IL-17A and IL-22 secretion at the end stage of chronic lung diseases remains largely unexplored. In order to uncover tissue- and disease-specific secretion patterns, we compared production patterns of IL-17A and IL-22 in three different human end-stage lung disease entities. Methods Production of IL-17A, IL-22 and associated cytokines was assessed in supernatants of re-stimulated lymphocytes by multiplex assays and multicolour flow cytometry of conventional T cells, iNKT cells, γδ T cells and innate lymphoid cells in bronchial lymph node and lung tissue from patients with emphysema (n = 19), idiopathic pulmonary fibrosis (n = 14) and cystic fibrosis (n = 23), as well as lung donors (n = 17). Results We detected secretion of IL-17A and IL-22 by CD4+ T cells, CD8+ T cells, innate lymphoid cells, γδ T cells and iNKT cells in all end-stage lung disease entities. Our analyses revealed disease-specific contributions of individual lymphocyte subpopulations to cytokine secretion patterns. We furthermore found the high levels of microbial detection in CF samples to associate with a more pronounced IL-17A signature upon antigen-specific and unspecific re-stimulation compared to other disease entities and lung donors. Conclusion Our results show that both adaptive and innate lymphocyte populations contribute to IL-17A-dependent pathologies in different end-stage lung disease entities, where they establish an IL-17A-rich microenvironment. Microbial colonisation patterns and cytokine secretion upon microbial re-stimulation suggest that pathogens drive IL-17A secretion patterns in end-stage lung disease.
Gesehen am 29.07.2022